Internationalization of Higher Education and Research in Ethiopia: Considerations for Institutional Strategy - Woldegiyorgis, Ayenachew Assefa (Bahir Dar Journal of Education, 2018)
In Ethiopia, research is not only small in size but also largely set as a component of the higher education system. Therefore, policy and strategic decisions at national level are often developed in blended manner that encompasses both aspects. Internationalization has for the first time emerged as a policy issue in the fifth Education Sector Development Program, in which research also gained attention, though less than deserved. This paper examines the practice of internationalization of higher education at institutional level and the existing loose-defined policy space. Finally, the paper outlines possible institutional strategies for the internationalization of research.